Epigenetic regulatory mechanisms induced by resveratrol - Fernandes, Guilherme Felipe Santos [UNESP] (2017)
Resveratrol (RVT) is one of the main natural compounds studied worldwide due to its potential therapeutic use in the treatment of many diseases, including cancer, diabetes, cardiovascular diseases, neurodegenerative diseases and metabolic disorders. Nevertheless, the mechanism of action of RVT in all of these conditions is not completely understood, as it can modify not only biochemical pathways but also epigenetic mechanisms. In this paper, we analyze the biological activities exhibited by RVT with a focus on the epigenetic mechanisms, especially those related to DNA methyltransferase (DNMT), histone deacetylase (HDAC) and lysine-specific demethylase-1 (LSD1).